HCV Council - Critical Appraisal of Data: Recommendations for Clinical Practice in a Rapidly Evolving Therapeutic Landscape. - Reau, Nancy; Fried, Michael W; Nelson, David R; Brown, Robert S; Everson, Gregory T; Gordon, Stuart C; Jacobson, Ira M; Lim, Joseph K; Pockros, Paul J; Reddy, K Rajender; Sherman, Kenneth E (Liver international : official journal of the International Association for the Study of the Liver, 2015)
The HCV Council 2014, like its predecessor HCV Council 2011, assembled leading clinicians and researchers in the field of hepatitis C to critically evaluate current data regarding best practices for managing patients with chronic hepatitis C virus (HCV). Clinical practice statements were developed that reflect areas of potential controversy with high clinical impact. Faculty members were responsible for reviewing the literature to support or reject these statements. After a review and comprehensive discussion of the data, the HCV Council faculty voted on the nature of the evidence and the level of support for each statement. The results of the detailed analysis with expert opinion are summarized in this article. This article is protected by copyright. All rights reserved.